The Heuristic Learning Model To Critical Thinking Ability In Elementary Science Study - Fatimah; Risda Amini; Yanti Fitria (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
Critical thinking is an ability that can create positive things, have broad insights, and can actualize meaningful knowledge. Through interesting and creative learning models, critical thinking can be created in fun learning. The implementation of this research activity is to develop students' critical thinking skills in elementary science learning. The research method uses Qualitative Research using classroom action research. the research sample of class IV students totaling 22 students. This research was conducted on June 21 - 26 2022 carried out online in three cycles. Cycle I was held on June 22, 2022, Cycle II on June 25, 2022, and Cycle III on June 26, 2022. The results showed that students' critical thinking skills were measured through tests made based on critical thinking indicators which increased in each cycle. In Cycle I it achieved an average score of 75.5. Cycle II achieved an average score of 78.3. And in Cycle III it achieved an average score of 82.5. Based on the results of this study it can be concluded that the Heuristic learning model can be used so that students have the ability to think critically in learning so that they can create situations that are more responsive and stimulate students to think.